The impact of next generation sequencing technologies on haematological research – A review. Issue 1 (2015) - Black, Jessica S.; Salto-Tellez, Manuel; Mills, Ken I.; Catherwood, Mark A.
Abstract: Next-generation sequencing (NGS) technologies have begun to revolutionize the field of haematological malignancies through the assessment of a patient's genetic makeup with a minimal cost. Significant discoveries have already provided a unique insight into disease initiation, risk stratification and therapeutic intervention. Sequencing analysis will likely form part of the routine diagnostic testing in the future. However, a number of important issues need to be addressed for that to become a reality with regard to result interpretation, laboratory workflow, data storage and ethical issues. In this review we summarize the contribution that NGS has already made to the field of haematological malignancies. Finally, we discuss the challenges that NGS technologies will bring in relation to data storage, ethical and legal issues and laboratory validation. Despite these challenges, we predict that high-throughput DNA sequencing will redefine haematological malignancies based on individualized genomic analysis.